1998
DOI: 10.1136/gut.43.5.699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial on the effect of regular tea drinking on iron accumulation in genetic haemochromatosis

Abstract: Background-Black tea is known to be a potent inhibitor of intestinal absorption of non-haem iron at least in healthy subjects. Aims-To investigate this eVect in patients with genetic haemochromatosis, and, more importantly, the eVect of regular tea drinking on the accumulation of storage iron in these patients over one year. Patients-Investigations were carried out on 18 patients with clinically proven genetic haemochromatosis. For the study of storage iron accumulation, they were separated into a group instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 20 publications
1
50
2
2
Order By: Relevance
“…A common custom in Egypt is to drink nearly 2 g/250 mL of red tea right after each meal particularly after lunch. Numerous studies reported that tea hinders iron absorption and advised tea drinkers to have their cups at least 1 h after meal [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…A common custom in Egypt is to drink nearly 2 g/250 mL of red tea right after each meal particularly after lunch. Numerous studies reported that tea hinders iron absorption and advised tea drinkers to have their cups at least 1 h after meal [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Имеются указания на то, что при врожденном гемохроматозе полифенолы и оксалаты, содержащиеся в чёрном чае и нецитрусовых фруктах, могут ингибировать адсорбцию негемового железа, способствуя повышению уровня гепсидина [24][25][26][27].…”
Section: рисунок3unclassified
“…Iron stores in C282Y homozygotes are positively associated with high alcohol and low fresh fruit consumption [17] and regular tea drinking with meals reduces the frequency of phlebotomies [14]. The role of diet in the management of haemochromatosis is controversial as many haematologists consider regular phlebotomy to be less invasive than dietary modification and therefore more acceptable for their patients.…”
Section: Diet Genotype and Phenotypementioning
confidence: 99%